Organic Stereochemistry. Part 31. Issue 3 (13th March 2013) - Testa, Bernard
Abstract This review continues a general presentation of the principles of stereochemistry with special reference to medicinal compounds. Here, we discuss further stereogenic elements other than the stereogenic centers presented in Part 2. These are the axis of chirality, the plane of chirality, helicity, and (E, Z)‐diastereoisomerism (stereoisomerism about double bonds). Some of these elements of stereoisomerism are not always well understood, and they raise specific convention issues. Isomerization reactions will also be discussed. As far as possible, the examples we present have biochemical and mainly medicinal relevance; a systematic overview concerning biosystems will be presented in Parts 5–8.